A review of turbulent skin-friction drag reduction by near-wall transverse forcing - Ricco, Pierre; Skote, Martin; Leschziner, Michael A. (Elsevier, 2021)
The quest for reductions in fuel consumption and CO2 emissions in transport has been a powerful driving force for scientific research into methods that might underpin drag-reducing technologies for a variety of vehicular transport on roads, by rail, in the air, and on or in the water. In civil aviation, skin-friction drag accounts for around 50% of the total drag in cruise conditions, thus being a preferential target for research. With laminar conditions excluded, skin friction is intimately linked to the turbulence physics in the fluid layer closest to the skin. Hence, research into drag reduction has focused on methods to depress the turbulence activity near the surface. The most effective method of doing so is to exercise active control on the near-wall layer by subjecting the drag-producing ow in this layer to an unsteady and/or spatially varying cross-ow component, either by the action of transverse wall oscillations, by embedding rotating discs into the surface or by plasma-producing electrodes that accelerate the near-wall fluid in the transverse direction. In ideal conditions, drag-reduction margins of order of 50% can thereby be achieved. The present article provides a near-exhaustive review of research into the response of turbulent near-wall layers to the imposition of unsteady and wavy transverse motion. The review encompasses experiments, simulation, analysis and modelling, mainly in channel flows and boundary layers. It covers issues such as the drag-reduction margin in a variety of actuation scenarios and for a wide range of actuation parameters, the underlying physical phenomena that contribute to the interpretation of the origin of the drag reduction, the dependence of the drag reduction on the Reynolds number, passive control methods that are inspired by active control, and a forward look towards possible future research and practical realizations. The authors hope that this review, by far the most extensive of its kind for this subject, will be judged as a useful foundation for future research targeting friction-drag reduction.
Keywords: Spanwise wall forcing; Turbulent drag reduction